Antigenic Determinants of SARS-CoV-2-Specific CD4+ T Cell Lines Reveals M Protein-Driven Dysregulation of Interferon Signaling - Gazzinelli-Guimaraes, Pedro H.; Sanku, Gayatri; Sette, Alessandro; Weiskopf, Daniela; Schaughency, Paul; Lack, Justin; Nutman, Thomas B. (Frontiers in Immunology, 2022)
We generated CD4+ T cell lines (TCLs) reactive to either SARSCoV-2 spike (S) or membrane (M) proteins from unexposed naïve T cells from six healthy donor volunteers to understand in fine detail whether the S and M structural proteins have intrinsic differences in driving antigen-specific CD4+ T cell responses. Having shown that each of the TCLs were antigen-specific and antigen-reactive, single cell mRNA analyses demonstrated that SARS-CoV-2 S and M proteins drive strikingly distinct molecular signatures. Whereas the S-specific responses are virtually indistinguishable from those responses induced by other viral antigens (e.g. CMV), the M protein-specific CD4+ TCLs have a transcriptomic signature that indicate a marked suppression of interferon signaling, characterized by a downregulation of the genes encoding ISG15, IFITM1, IFI6, MX1, STAT1, OAS1, IFI35, IFIT3 and IRF7 (a molecular signature which is not dissimilar to that found in severe COVID-19). Our study suggests a potential link between the antigen specificity of the SARS-CoV-2-reactive CD4+ T cells and the development of specific sets of adaptive immune responses. Moreover, the balance between T cells of significantly different specificities may be the key to understand how CD4+ T cell dysregulation can determine the clinical outcomes of COVID-19.